Understanding in the Context of Sensual Perception - YERZNKYAN, YELENA; MOVSISYAN, DIANA (Bulletin of Yerevan University B: Philology, 2021)
The article discusses the process of understanding in the light of sensual perceptions. On the basis of both English and Armenian verbs of perception, it is shown that understanding is embodied and is preconditioned by seeing, hearing and sensing. The study also shows that the process of understanding necessarily requires evaluation of the communicated information and is emotionally coloured.
Keywords: understanding, embodiment, sensing, seeing, hearing, evaluation, attitude, emotionality